Clinical research during the COVID-19 pandemic: The role of virtual visits and digital approaches. Issue 1 (8th March 2021) - Loucks, Tammy L.; Tyson, Clare; Dorr, David; Garovic, Vesna D.; Hill, James; McSwain, S. David; Radovick, Sally; Sonnenberg, Frank A.; Weis, Jennifer A.; Brady, Kathleen T.
Abstract: Clinical trials are a fundamental tool in evaluating the safety and efficacy of new drugs, medical devices, and health system interventions. Clinical trial visits generally involve eligibility assessment, enrollment, intervention administration, data collection, and follow-up, with many of these steps performed during face-to-face visits between participants and the investigative team. Social distancing, which emerged as one of the mainstay strategies for reducing the spread of SARS-CoV-2, has presented a challenge to the traditional model of clinical trial conduct, causing many research teams to halt all in-person contacts except for life-saving research. Nonetheless, clinical research has continued during the pandemic because study teams adapted quickly, turning to virtual visits and other similar methods to complete critical research activities. The purpose of this special communication is to document this rapid transition to virtual methodologies at Clinical and Translational Science Awards hubs and highlight important considerations for future development. Looking beyond the pandemic, we envision that a hybrid approach, which implements remote activities when feasible but also maintains in-person activities as necessary, will be adopted more widely for clinical trials. There will always be a need for in-person aspects of clinical research, but future study designs will need to incorporate remote capabilities.